Characterization of CdS and ZnS Nanoparticle Semiconductors: for Optoelectronics Application - Suryajaya Suryajaya; A.V. Nabok; A. K. Hassan; A. Tsargorodskaya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2011)
In this work, CdS and ZnS semiconducting colloid nanoparticles coated with organic shell, containing either SO−3 or NH+ 2 groups, were deposited as thin films using the technique of electrostatic self-assembly. The films produced were characterized with UV-vis spectroscopy - for optical properties; mercury probe - for electrical characterisation; and photon counter - for electroluminescence study. UV-vis spectra show a substantial blue shift of the main absorption band of both CdS and ZnS, either in the form of solutions or films, with respect tothe bulk materials. The calculation of nanoparticles’ radii yields the value of about 1.8 nm for both CdS and ZnS. Current-voltage (I-V) and capacitance-frequency (C-f) measurements of polyelectrolyte/nanoparticles (CdS or ZnS) films suggest the tunnelling behaviour in the films while capacitance- voltage (C-V) and conductancevoltage (G-V) measurements suggest that these nanoparticles are conductive. The electroluminescence was detected in sandwich structures of (PAH/CdS/PAH)N using a photon counting detector, but not in the case of ZnS films.